Performance Analysis of District Election Commission Employees - Fitrasari, Bela Mulia; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2023)
This study employs a qualitative description method to analyze the performance of Sidoarjo District General Election Commission employees, focusing on commissioners and various administrative roles. Utilizing interviews, observation, and documentation, the interactive data analysis model by Miles and Huberman is applied. Findings reveal commendable performance across indicators, yet highlight a notable issue with punctuality. Despite disciplined office hours, employees exhibit lower punctuality during activities and office entry. Limited working hours appear to shape their engagement, with perceived inactivity outside election periods. Various factors impede employee work at the General Election Commission in Sidoarjo Regency. This research contributes valuable insights into electoral administration, emphasizing punctuality and addressing challenges faced by commission employees Highlight : Insights into Employee Punctuality: Reveals significant variations in punctuality during activities and office entry, providing a nuanced understanding of employee behavior. Limited Working Hours Impact: Examines the influence of limited working hours on employee engagement, shedding light on the perceived inactivity outside election periods. Addressing Challenges in Electoral Administration: Highlights key factors hindering the work of General Election Commission employees, offering actionable insights for improving electoral processes. Keywords: Election Commission, Employee Performance, Punctuality, Qualitative Analysis, Challenges